Construcciones visuales y memorias de la dictadura de Pinochet a través de películas y reportajes extranjeros (1973-2013) - Marcy Campos Pérez (Amnis)
This paper analyzes the relation between images and the representation of history throughout a set of movies and documentaries describing the Chilean dictatorship that were produced outside the country. It studies how these images contributed not only to the dissemination of visual information about certain crucial events during the military dictatorship, but also to their visual construction. It argues that, as a result of censorship and the lack of images, two main characteristics of authoritarian regimes, these productions acquired a particular value, becoming archival images or visual testimonies that will be used during the post-dictatorship era as visual references for historical reconstructions. The movies, reports, and television series about the dictatorship made after 1988 continuously addressed the conflicts surrounding memory, thus creating specific visual ways to approach Chile’s recent past.